Chick Ciliary Ganglion Neurons Contain Transcripts Coding for Acetylcholine Receptor-Associated Protein at Synapses (Rapsyn) - Burns, Aime L. (J Neurosci, 1997)
A peripheral membrane protein of ≈43 kDa (rapsyn) clusters muscle nicotinic acetylcholine receptors (AChRs), but molecules relevant to clustering neuronal AChRs have not been identified. Here, we have detected rapsyn transcripts in the chick nervous system, localized rapsyn mRNA in ciliary ganglion (CG) neurons, which are known to cluster AChRs, and identified three rapsyn cDNAs derived from the ganglion. Our initial Northern blots, performed using a mouse probe, revealed rapsyn-like transcripts in chick muscle and brain. To develop species-specific probes, we prepared a chick rapsyn cDNA construct, Ch43K.1, that encodes a protein having extensive homology to mouse rapsyn. Using primers designed to anneal near the 5′ and 3′ boundaries of Ch43K.1, three prominent cDNAs were amplified from chick muscle templates by reverse transcriptase based-PCR. Products of similar size were also amplified using cDNA prepared from neuronal tissues expected to contain clustered AChRs (CG and brain), whereas none were detected using templates from tissues not displaying clustered AChRs (sensory ganglia and liver). In situ hybridization confirmed that rapsyn mRNA is expressed both in chick muscle fibers and in CG neurons. Sequencing the three cDNAs amplified from CG templates revealed the largest to be Ch43K.1, whereas the smaller two may represent splice variants. These findings suggest that multiple rapsyn-like molecules are involved in clustering the distinct AChRs expressed by muscle fibers and neurons.